Desarrollo de la creatividad en las clases virtuales de los niños de educación inicial del subnivel ii de la unidad educativa Francisco Huerta Rendón atreves del uso de los ambientes de aprendizaje - Sánchez Parrales, Génesis Alexandra (2021)
Summary Initial education is the phase in which children begin educational units in order to be part of the first phase of knowledge achievement since it appropriates various knowledge provided by the teacher but unfortunately nowadays due to the covid-19 Classes are online for children to develop their skills in their homes with the help of parents or representatives, however it is considered that early childhood education is currently allowing children to have knowledge from their homes. It should be stated that the acquisition of knowledge by children has been discouraged because there is a mandatory quarantine but rather that teachers have sought methodologies, technicians so that they can acquire knowledge of children such is the case that in the units educational institutions in Ecuador have made use of the Microsoft Team platform or other applications so that children can function in an environment that generates comfort and can use technologies in their favor, so it has been seen that children are acquiring knowledge in their homes. Various tools and techniques must be implemented so that children acquire knowledge and in turn develop their psychomotor skills as well as their intellectual capacity in terms of their education since the virtual modality is currently used frequently for the acquisition and teaching of learning.